Microbiological analysis of bacterial pathogens in poultry feeds and water resources in Blouberg Poultry Value Chain Project, Limpopo Province, South Africa - Ngwenya, Lloyd (My University, 2019)
Poultry is a good source of animal protein for many households due to its affordability. However, it is prone to bacterial infections which can be passed on to consumers, hence chickens that are reared without constant health checks present a potential health threat to humans. The objective of the study was to identify the zoonotic bacterial pathogens in poultry feeds and water resources in Blouberg poultry value chain project. A total of 88 samples comprising of 14 feed samples, 14 water samples, 60 mouth and rectal swab samples were collected from the farms. The samples were screened for the presence of Escherichia coli, Salmonella spp. and Shigella spp. through selective cultivation. Only coliforms and the dominant isolates were identified as Escherichia coli, Klebsiella spp., and Enterobacter spp., Salmonella and Shigella spp. were not detected in all the samples. E. coli strains that were isolated from the water sources and mouth and rectal swabs of the chickens showed a significant resistance to gentamycin, neomycin, penicillin, streptomycin, tetracycline, erythromycin, nalidixic acid, ciprofloxacin and ampicillin (p<0.05). Klebsiella pneumoniae showed resistance to neomycin; penicillin; erythromycin (p<0.05) while K. oxytoca and E. absuriae showed similar antibiotic resistance profile as penicillin, erythromycin, nalidixic acid and ampicillin. E. coli and K. pneumonia are mostly implicated in poultry disease outbreaks and they are enteric pathogens in humans as well. The presence of pathogens in poultry presents a great risk of secondary infection in humans and this will lead to socio-economic problems for the affected communities. The information generated in this study will guide the relevant stakeholders who handle poultry feeds and water resources in following good management practices. 1
Thesis (M.Sc. Agriculture (Animal Production)) -- University of Limpopo, 2019
Keywords: Food-borne disease; Zoonotic pathogens; Antibiotic resistance; Bacterial isolates; Foodborne diseases -- South Africa -- Limpopo; Poultry -- Disease -- South Africa -- Limpopo; Poultry -- Pathogens; Drug resistance in microorganisms